2010
DOI: 10.1115/1.4000485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Suction and Injection Purge-Flow on the Secondary Flow Structures of a High-Work Turbine

Abstract: In high-pressure turbines, a small amount of air is ejected at the hub rim seal to cool and prevent the ingestion of hot gases into the cavity between the stator and the disk. This paper presents an experimental study of the flow mechanisms that are associated with injection through the hub rim seal at the rotor inlet. Two different injection rates are investigated: nominal sucking of −0.14% of the main massflow and nominal blowing of 0.9%. This investigation is executed on a one-and-1/2-stage axial turbine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The increased strength of the rotor hub passage vortex and the increased penetration depth of flow with negative incidence has been reported by Ong et al (2012). Schuepbach et al (2010) reported on a decrease of efficiency by 0.6% per percent of injected purge mass flow based on measurements in a 1.5-stage high-pressure turbine. Zlatinov et al (2012) performed a combined study on hub and shroud leakage loss mechanisms, highlighting that by 1.5% of purge flow injection at the hub, turbine losses are increased by 12%.…”
Section: Introductionmentioning
confidence: 61%
“…The increased strength of the rotor hub passage vortex and the increased penetration depth of flow with negative incidence has been reported by Ong et al (2012). Schuepbach et al (2010) reported on a decrease of efficiency by 0.6% per percent of injected purge mass flow based on measurements in a 1.5-stage high-pressure turbine. Zlatinov et al (2012) performed a combined study on hub and shroud leakage loss mechanisms, highlighting that by 1.5% of purge flow injection at the hub, turbine losses are increased by 12%.…”
Section: Introductionmentioning
confidence: 61%
“…At a fixed mass flow ratio, increasing the circumferential velocity relative to the rotor also reduced the stage efficiency due to a decrease in the near-wall incidence angle to the rotor. Increasing statorrotor leakage flow resulted in higher dissipation around the passage vortex and lower overall efficiency in rotating rig measurements by Schuepbach, et al [10]. McLean, et al [11] found that coolant injection into the stator-rotor wheelspace generally decreased total-to-total stage efficiency, although discrete-hole coolant injection on the stator hub improved stage efficiency by energizing the stator airfoil wake and the rotor hub boundary layer.…”
Section: Review Of Relevant Literaturementioning
confidence: 98%
“…Additionally, the mixing of the exiting cold gas with the main flow and its interaction with secondary flow structures, such as the vane hub passage vortex, causes further aerodynamic losses. The later has, for example, been investigated by Schuepbach et al (2010) and Schädler et al (2016).…”
Section: Introductionmentioning
confidence: 99%